Raging clouds - Yudori (Fantagraphics Books, 2025)
"Amélie is a brilliant woman trapped in the restricting social mores of high Dutch society in the mid-16th century. Her marriage to Hans, a swashbuckling merchant, is a terrible match. While he charms the townsfolk, at home he is her intellectual inferior and treats her with cruelty and sexual violence. Expected to be a devoted housewife, Amélie can only be her true, free-spirited self when Hans travels away on business -- when she can explore the town alone, lose herself in literature, and study winged animals to learn about the mechanics of flight. She looks to the skies and dreams of flying far away. Her life changes when Hans returns from his journey with Sahara, a slave mistress from a distant land. The two women are drawn to each other -- each recognizing their confinement in a world dominated by men -- and work together to seek their freedom." --